Dreiser's Russian diary - Dreiser, Theodore, 1871-1945 (Dreiser, Theodore, 1871-1945. Works. 1988., 1996)
Theodore Dreiser's Russian Diary is an extended record of the American writer's travels throughout the Soviet Union in 1927-28. Dreiser was initially invited to Moscow for a week-long observance of the tenth anniversary of the October Revolution. He asked, and was granted, permission to make an extended tour of the country.This previously unpublished diary is a firsthand record of life in the USSR during the 1920s as seen by a leading American cultural figure. It is a valuable primary source, surely among the last from this period of modern history.